Literature Review: Potential of Jamblang (Syzygium Cumini (L.) Skeels) Plants as Nephroprotectors Based on Active Compound - Hidayah, Himyatul; Srifitriani, Erna; Atqia Shakira, Nabilla; Oktaviani Rahayu, Muthia; Mulyawan, Indra; Fatmawati, Frida (Rifa'Institute, 2022)
Introduction: Since ancient times, the jamblang plant (Syzygium Cumini (L.) has been used for traditional medicine in various regions to treat various diseases. Scientifically, this plant has proven its potential in curing blood sugar diseases. In addition to diabetes, other diseases that this plant can empirically overcome include thrush, sore throat and respiratory tract, diarrhea or dysentery and other stomach diseases, as well as a burn medicine. Another benefit of this plant is as an antibacterial, anti-inflammatory, antioxidant, antifungi, antiviral, antiallergic, antipyretic, antineoplastic. Objective: To know the benefits of jamblang fruit as a traditional medicine to cure some diseases. Method: In this study, the author used the literature review research method. Result and Discussion: In this study, it has been proven that jamblang fruit can be used as a traditional medicine that can cure fever, stomach pain, indigestion and anti-diabetes mellitus. Conclusion: it can be concluded that the potential in jamblang plants (Syzygium cumini (L.) Skeels) as Neproprotective which contains active compounds. In the content of active compounds there are thirteen groups of active compounds in jamblang leaves, namely: flavonoids, phenyl propanoids, phenols, tannins, glucosides, lignans, triterpenoids, sequiterpenoids, sterols, benzofurans, chromones, coumarins and benzoic acid